Bivalve Molluscs as Model Systems for Studying Mitochondrial Biology. (4th May 2021) - Ghiselli, Fabrizio; Iannello, Mariangela; Piccinini, Giovanni; Milani, Liliana
Synopsis: The class Bivalvia is a highly successful and ancient taxon including ∼25, 000 living species. During their long evolutionary history bivalves adapted to a wide range of physicochemical conditions, habitats, biological interactions, and feeding habits. Bivalves can have strikingly different size, and despite their apparently simple body plan, they evolved very different shell shapes, and complex anatomic structures. One of the most striking features of this class of animals is their peculiar mitochondrial biology: some bivalves have facultatively anaerobic mitochondria that allow them to survive prolonged periods of anoxia/hypoxia. Moreover, more than 100 species have now been reported showing the only known evolutionarily stable exception to the strictly maternal inheritance of mitochondria in animals, named doubly uniparental inheritance. Mitochondrial activity is fundamental to eukaryotic life, and thanks to their diversity and uncommon features, bivalves represent a great model system to expand our knowledge about mitochondrial biology, so far limited to a few species. We highlight recent works studying mitochondrial biology in bivalves at either genomic or physiological level. A link between these two approaches is still missing, and we believe that an integrated approach and collaborative relationships are the only possible ways to be successful in such endeavor.